Regionality Marks for Facial Conformation Modeling - Vila Nova, Arnaldo Barreto; Vidal, Creto Augusto; Cavalcante-Neto, Joaquim B.; Carneiro, Lilian de Oliveira (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Accurate representation and manipulation of human facial geometry present critical challenges in computer graphics, biometrics, medical imaging and virtual reality applications. This study introduces a novel facial conformation modeling technique that leverages linear anthropometric measurements and geodesic distance-based regionality marks to achieve anatomically precise and scalable deformations. By defining individualized influence zones for craniofacial landmarks, the method minimizes interference between facial regions and enhances morphological variability. The expanded parameter set, comprising 34 measurements around 30 landmarks, enables detailed and intuitive facial modeling. Applications in virtual reality include personalized avatar generation, clinical facial analysis, and identity verification systems. Visual results demonstrate the method’s ability to adapt to diverse facial anatomies, ensuring realistic and customizable facial models for immersive environments.